2016
DOI: 10.1021/acsnano.6b05910
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Tamoxifen Resistance of Human Breast Cancer by Targeted Gene Silencing Using Multifunctional pRNA Nanoparticles

Abstract: Most breast cancers express estrogen receptor (ER) α, and the antiestrogen drug tamoxifen has been widely used for their treatment. Unfortunately, up to half of all ERα-positive tumors have intrinsic or acquired endocrine therapy resistance. Our recent studies revealed that the ER coactivator Mediator Subunit 1 (MED1) plays a critical role in tamoxifen resistance through cross-talk with HER2. Herein, we assembled a three-way junction (3-WJ) pRNA–HER2apt–siMED1 nanoparticle to target HER2-overexpressing human b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 57 publications
2
109
0
Order By: Relevance
“…In addition, substituting uridine and cytidine with their 2 ′ -fluoro-modified counterparts further increases nanoparticle stability and prevents digestion by RNases (Layzer et al 2004). 2 ′ -F modified phi29 pRNA 3WJ thus greatly enhances the thermodynamic and enzymatic stability of RNA nanoparticles and has paved the way for medical applications of RNA nanotechnology (Cui et al 2015;Shu et al 2015;Binzel et al 2016b;Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, substituting uridine and cytidine with their 2 ′ -fluoro-modified counterparts further increases nanoparticle stability and prevents digestion by RNases (Layzer et al 2004). 2 ′ -F modified phi29 pRNA 3WJ thus greatly enhances the thermodynamic and enzymatic stability of RNA nanoparticles and has paved the way for medical applications of RNA nanotechnology (Cui et al 2015;Shu et al 2015;Binzel et al 2016b;Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…57 Unfortunately, up to half of ERα-positive tumors have intrinsic or acquired endocrine therapy resistance. 58 Previous studies claimed that E2 inhibits NF-κB-mediated gene transcription, 59,60 and decreased activity of p65 induced by E2 is due to the cytoplasmic sequestration of this transcription factor. 55 Our results showed that LINC00263 is expressed at lower levels in female patients than in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the RNA tetrahedrons hold a great potential to serve as a multifunctional nanocarrier for cancer therapy. Zhang and coworkers designed 3WJ‐pRNA‐based nanoparticles for treating breast cancers with tamoxifen resistance (Figure b) . The cross‐talk between coactivator Mediator Subunit 1 (MED1) and HER2 that overexpressed on the cell membrane of human breast cancer cells played a crucial role in the mechanism of tamoxifen resistance .…”
Section: Gene Therapymentioning
confidence: 99%
“…b) RNA nanoparticles for gene therapy aimed at drug resistant cancer cells. Adapted with permission . Copyright 2016, American Chemical Society.…”
Section: Gene Therapymentioning
confidence: 99%